Approach to the Diagnosis of Bleeding Disorders in Children - Tawfique, Muhammad (Community Based Medical Journal, 2021)
Hemostasis is the cessation of bleeding in the intravascular compartment. This occurs by the formation of clot formation at the site of injury. The intricately related system also regulates the size of the clots by the activation of fibrinolysis. The disorders that lead to the bleeding outside the intravascular space is bleeding disorder. Bleeding occurs as a result of defective quality or quantitative deficiencies of platelets, coagulation problems in the extrinsic or intrinsic or the common pathways and abnormalities in the vascular walls to contain hemorrhage. Although the values of different coagulation and fibrinlytic factors are pretty much like that of the adults yet, neonates have considerable differences in these values than their senior counterparts even in pediatric age groups. Considering all these facts the history, physical examination and laboratory investigations always provide the clinicians some important clues to reach the diagnosis. Because of the complicated relationship among the different pathways of coagulations and fibrinolytic systems the whole procedure might look complex yet methodical approach paves the way of an intelligent clinician to arrive at the diagnosis with precision and clinical perfection. CBMJ 2020 July: Vol. 09 No. 02 P: 45-53